Genotoxic effect of a binary mixture of dicamba- and glyphosate-based commercial herbicide formulations on Rhinella arenarum (Hensel, 1867) (Anura, Bufonidae) late-stage larvae - Soloneski, Sonia María Elsa (2016)
The acute toxicity of two herbicide formulations, namely, the 57.71 % dicamba (DIC)-based Banvel® and the 48 % glyphosate (GLY)-based Credit®, alone as well as the binary mixture of these herbicides was evaluated on late-stage Rhinella arenarum larvae (stage 36) exposed under laboratory conditions. Mortality was used as an endpoint for determining acute lethal effects, whereas the single-cell gel electrophoresis (SCGE) assay was employed as genotoxic endpoint to study sublethal effects. Lethality studies revealed LC50₉₆ ₕ values of 358.44 and 78.18 mg L⁻¹ DIC and GLY for Banvel® and Credit®, respectively. SCGE assay revealed, after exposure for 96 h to either 5 and 10 % of the Banvel® LC50₉₆ ₕ concentration or 5 and 10 % of the Credit® LC50₉₆ ₕ concentration, an equal significant increase of the genetic damage index (GDI) regardless of the concentration of the herbicide assayed. The binary mixtures of 5 % Banvel® plus 5 % Credit® LC50₉₆ ₕ concentrations and 10 % Banvel® plus 10 % Credit® LC50₉₆ ₕ concentrations induced equivalent significant increases in the GDI in regard to GDI values from late-stage larvae exposed only to Banvel® or Credit®. This study represents the first experimental evidence of acute lethal and sublethal effects exerted by DIC on the species, as well as the induction of primary DNA breaks by this herbicide in amphibians. Finally, a synergistic effect of the mixture of GLY and DIC on the induction of primary DNA breaks on circulating blood cells of R. arenarum late-stage larvae could be demonstrated.